Internment Poster/Broadside: "Instructions to All Persons of Japanese Ancestry," 1942 (1942)
Internment Poster/Broadside titled "Instructions to All Persons of Japanese Ancestry Living in ... the Counties of Santa Barbara and San Luis Obispo" issued by the Western Defense Command and 4th Army (U.S. Army), at the Presidio of San Francisco giving official notice and instructions to Japanese-Americans living in specific portions of the West Coast on their forced evacuation to internment camps. Dated to April 23rd, 1942.